CORRELATION OF DISASTER MITIGATION WITH COMMUNITY PREPAREDNESS ATTITUDES IN FACING FLOOD DISASTERS IN CITEUREUP VILLAGE WEST JAVA - Mufidah, Farah; Haryeti, Popon; Ayu Prameswari (Buletin Veteriner Udayana, 2024)
Flooding is one of the most common disasters in Bandung Regency and has become an annual event during the rainy season. Areas in Bandung Regency where flooding often occurs every year are in Dayeuhkolot District, Baleendah District, and Bojongsoang District. This includes Citeureup Village in Dayeuhkolot Sub-district. Lack of preparedness in the face of disaster is one of the causes of the high impact of damage or loss after a disaster. Thus, optimal disaster mitigation is needed in cases where the community has a low level of preparedness, so that efforts to reduce disaster risk increase. The purpose of this study was to determine whether there is a relationship between mitigation and community preparedness attitudes in facing flood disasters in Citeureup Village, Dayeuhkolot District. This research uses quantitative methods with correlational research design. The sampling technique is using Cluster Random Sampling with a sample size of 67 respondents. Data analysis using Pearson's correlation using JASP software. The results obtained are the correlation coefficient obtained with an r value of 0.696 with a p-value of 0.001, then H0 is rejected and H1 is accepted which shows a significant relationship between disaster mitigation and community preparedness attitudes in the face of flood disasters. The shape of the relationship between these two variables is positive, meaning that the more